Mallarmé The Poet and His Circle - Lloyd, Rosemary (Cornell University Press, 2018)
Upon his death in 1898, the French Symbolist poet Stephane Mallarmé (b. 1842) left behind a body of published work which though modest in quantity was to have a seminal influence on subsequent poetry and aesthetic theory. He also enjoyed an unparalleled reputation for extending help and encouragement to those who sought him out. Rosemary Lloyd has produced a fascinating literary biography of the poet and his period, offering a subtle exploration of the mind and letters of one of the giants of modern European poetry.Every Tuesday, from the late 1870s on, Mallarmé hosted gatherings that became famous as the "Mardis" and that were attended by a cross section of significant writers, artists, thinkers, and musicians in fin-de-siecle France, England, and Belgium. Through these gatherings and especially through a voluminous correspondence—eventually collected in eleven volumes—Mallarmé developed and recorded his friendships with Paul Valery, Andre Gide, Berthe Morisot, and many others. Attractively written and scrupulously documented, Mallarme: The Poet and His Circle is unique in offering a biographical account of the poet's literary practice and aesthetics which centers on that correspondence